Late Evaluation of Silent Cerebral Ischemia Detected by Diffusion-Weighted MR Imaging after Filter-Protected Carotid Artery Stenting - Palombo, G.; Faraglia, V.; Stella, N.; Giugni, E.; Bozzao, A.; Taurino, M. (American Journal of Neuroradiology, 2008)
BACKGROUND AND PURPOSE: Postoperative diffusion-weighted MR imaging (DWI) often discloses new lesions after carotid artery stent placement (CAS), most of them asymptomatic. Our aim was to investigate the fate of these silent ischemic lesions.MATERIALS AND METHODS: We prospectively studied 110 patients undergoing protected transfemoral CAS, 98 of whom underwent DWI before and after the intervention. Patients in whom DWI disclosed silent postoperative lesions also had delayed MR imaging. Preoperative, postoperative, and delayed scans were compared.RESULTS: Of the 92 patients without postoperative symptoms, DWI disclosed 33 new silent ischemic lesions in 14 patients (15.2%), 13 of whom (30 lesions) underwent delayed MR imaging after a mean follow-up of 6.2 months. In 8 of these 13 patients (61%), MR imaging disclosed 12 persistent lesions (12/30, 40%). The reversibility rate depended significantly on the location (cortical versus subcortical) and size (0–5 versus 5–10 mm) of the lesions (P < .05 by χ2 test).CONCLUSIONS: Because many silent ischemic lesions seen on postoperative DWI after CAS reverse within months, the extent of permanent CAS-related cerebral damage may be overestimated.